Pengaruh Growth Opportunity, Keputusan Investasi dan Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Healthcare yang Terdaftar di Bursa Efek Indonesia - Sutihat, Aat (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to examine the influence of growth opportunity, investment decisions and financial performance on company value in healthcare companies listed on the Indonesia Stock Exchange. The population in this study consisted of 27 healthcare companies listed on the Indonesian stock exchange during the 2017-2021 period. In carrying out the research, the data used was secondary data and the sampling technique used purposive sampling technique to obtain 8 healthcare companies that met the sample criteria. The regression model used in this research is a panel data regression model and was tested using the eviews 12 application with the f test (variance analysis), t test (significant test), and coefficient of determination test and panel data regression as analysis tools. The research results show that the independent variables jointly influence company value in the f test. In the t test, the growth opportunity variable and the company performance variable have a partial effect on company value and investment decisions do not have a significant effect on company value. And overall the independent variables are able to predict company value on a scale of 91,78%.